Handbook of longitudinal research methods in organisation and business studies - Hassett, Melanie E., editor; Paavilainen-Mñtymaki, Eriikka, editor (Cheltenham : Edward Elgar Pub. Ltd., 2013)
Includes bibliographical references and index